2016
DOI: 10.1038/nrdp.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media

Abstract: Otitis media (OM) or middle ear inflammation is a spectrum of diseases, including acute otitis media (AOM), otitis media with effusion (OME; 'glue ear') and chronic suppurative otitis media (CSOM). OM is among the most common diseases in young children worldwide. Although OM may resolve spontaneously without complications, it can be associated with hearing loss and life-long sequelae. In developing countries, CSOM is a leading cause of hearing loss. OM can be of bacterial or viral origin; during 'colds', virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
393
1
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(422 citation statements)
references
References 224 publications
(255 reference statements)
4
393
1
24
Order By: Relevance
“…Handzic and all showed ear side related differences of hearing loss in OME children with orofacial clefts and out of malformations. Previous studies indicated that CHL (conductive hearing loss) profoundly affects short term synaptic depression and spike adaptation, increases synaptic latencies and evoked postsynaptic potentials were longer and more variable [3]. Females have advantage in process of hearing, it was not described if there exist gender differences in sensitivity for hearing loss in case of prolonged presence of conductive hearing loss to the central auditory processing.…”
Section: Resultsmentioning
confidence: 99%
“…Handzic and all showed ear side related differences of hearing loss in OME children with orofacial clefts and out of malformations. Previous studies indicated that CHL (conductive hearing loss) profoundly affects short term synaptic depression and spike adaptation, increases synaptic latencies and evoked postsynaptic potentials were longer and more variable [3]. Females have advantage in process of hearing, it was not described if there exist gender differences in sensitivity for hearing loss in case of prolonged presence of conductive hearing loss to the central auditory processing.…”
Section: Resultsmentioning
confidence: 99%
“…Certain vitamin and dietary deficiencies can be found in cases of AOM and rOM; like vitamin A, zinc, EPA (an omega 3 fatty acid) and selenium deficiencies [13]. There are other risks factors that are related to AOM, like younger age [1,14], attendance to day care centers [3,8,10], prematurity [8], increased number of siblings, dummy use [1,8], Autumn and winter seasons [1], craniofacial anomaly [14], asthma [3] and atop [3,14] (Table 1). …”
Section: Pathogenesismentioning
confidence: 99%
“…The importance of other environmental factors cannot be underestimated in the pathogenesis of AOM; Paternal smoking is one of OM risk factors [1,3,8,10,14]; it causes mucosal inflammation, goblet hyperplasia and an increase in the production of mucus, by this it impairs mucosal immunity and increases bacterial colonization by enhancing bacterial binding to respiratory epithelium [1,10]. Children of mothers who smoked during pregnancy and stopped after delivery still have higher incidence of AOM [10].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis and retraining therapy for tinnitus have also seen breakthroughs [6]. Advances have been made in assessment of otitis media, and its classification and treatment [7]. A groundbreaking discovery in the pathogenesis of allergic rhinitis-allergic rhinitis and its impact on asthma (ARIA)-has redefined the classification of rhinitis and allergic rhinitis [8], and the mechanism and treatment of sinusitis [9].…”
mentioning
confidence: 99%